2006
DOI: 10.1097/01.wno.0000249318.88991.c4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroup Distribution in Pedigrees of Southeast Asian G11778A Leber Hereditary Optic Neuropathy

Abstract: To investigate the association of mitochondrial DNA (mtDNA) haplogroups and Leber hereditary optic neuropathy (LHON) in the Southeast Asian population, mtDNA haplogroup determination was performed by high-resolution restriction fragment length polymorphism in 42 patients with LHON who were carrying the G11778A mutation and in control subjects drawn from a Thai urban population unaffected by LHON. The patients with LHON were of Thai, Thai-Chinese, and Indian origin. Three mtDNA haplogroups, M, B*, and B, were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
2
9
1
1
Order By: Relevance
“…Other N and R macro-groups made up the remaining 20%. These frequencies are similar to those seen in HIV-negative Thai populations [3537]. Since DNA was available for all study participants, including those without ENFD, we were able to confirm that distribution of major mtDNA haplogroups did not differ significantly between those with and without ENFD data (data not shown).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Other N and R macro-groups made up the remaining 20%. These frequencies are similar to those seen in HIV-negative Thai populations [3537]. Since DNA was available for all study participants, including those without ENFD, we were able to confirm that distribution of major mtDNA haplogroups did not differ significantly between those with and without ENFD data (data not shown).…”
Section: Resultssupporting
confidence: 79%
“…Similar studies from HIV-infected persons of European ancestry have reported such differences [40,41]. Although population-based data from Thailand are limited, mtDNA haplogroup frequencies have been similar to those previously reported [3537], arguing against a significant impact of haplogroup on HIV acquisition risk. Nonetheless, the similar ENFD at baseline and ENFD gain on ART among the B haplogroup despite being older (and independent of other risk factors for ENFD change in this population) are notable and merit further study.…”
Section: Discussionsupporting
confidence: 82%
“…In the pooled Han Chinese from general populations, this haplogroup had a frequency of 16.7% (68/408), much higher than what we observed for the LHON subjects with m.14484T>C (1.9%; 1/52). This result was unexpected, but a extremely low occurrence of haplogroup F had been observed in Chinese LHON patients with m.11778G>A (2.2%; 4/182) [15] and in 40 LHON patients harboring m.11778G>A from Thailand (0%; 0/40) [38]. The exact reason for the low occurrence of haplogroup F in Chinese LHON families with m.14484T>C and m.11778G>A remains unclear.…”
Section: Discussionmentioning
confidence: 89%
“…Three of these families contained several people with the heteroplasmic mutation (F09, F24, F28), while the other family was homoplasmic (F30). All pedigrees belong to macrohaplogroup M (Tharaphan et al 2006).…”
Section: Resultsmentioning
confidence: 99%